UPAYA PENCEGAHAN STROKE PADA PENDERITA HIPERTENSI DENGAN MODEL TERAPI KELOMPOK (INTENSIVE PROBLEM SOLVING GROUP) DI WILAYAH PUSKESMAS KREMBANGAN SELATAN - Asnani .; Loetfia Dwi Rahariyani; Hilmi Yumni (Poltekkes Kemenkes Surabaya, 2015)
Stroke / evA are the symptoms of nervous system function deficits caused by cerebrovascular disease.One of the causes of stroke are hypertension. That people with hypertension do not have a stroke it isnecessary to make effective prevention group therapy model in the community at risk. The purpose ofresearch is to identify the prevention of stroke in hypertensive patients with group therapy models(Intensive Problem Solving Group). This research design